Structure-based discovery of LpxC inhibitors. Issue 8 (15th April 2017) - Zhang, Jing; Chan, Audrey; Lippa, Blaise; Cross, Jason B.; Liu, Christopher; Yin, Ning; Romero, Jan Antoinette C.; Lawrence, Jonathan; Heney, Ryan; Herradura, Prudencio; Goss, Jennifer; Clark, Cynthia; et al.
Graphical abstract: Abstract: The emergence and spread of multidrug-resistant (MDR) Gram negative bacteria presents a serious threat for public health. Novel antimicrobials that could overcome the resistance problems are urgently needed. UDP-3-O-( R -3-hydroxymyristol)- N -acetylglucosamine deacetylase (LpxC) is a cytosolic zinc-based deacetylase that catalyzes the first committed step in the biosynthesis of lipid A, which is essential for the survival of Gram-negative bacteria. Our efforts toward the discovery of novel LpxC inhibitors are presented herein.